Endoscopic full-thickness resection of polyps involving the appendiceal orifice: A multicenter international experience - Ichkhanian, Yervant; Barawi, Mohammed; Seoud, Talal; Thakkar, Shyam; Kothari, Truptesh H.; Halabi, Maan El; Ullah, Asad; Edris, Wedi; Aepli, Patrick; Kowalski, Thomas; Shinn, Brianna; Shariaha, Reem Z.; et al. (Endoscopy, 2021)
Background Endoscopic resection of lesions involving the appendiceal orifice remains a challenge. We aimed to report outcomes with the full-thickness resection device (FTRD) for the resection of appendiceal lesions and identify factors associated with the occurrence of appendicitis. Methods This was a retrospective study at 18 tertiary-care centers (USA 12, Canada 1, Europe 5) between November 2016 and August 2020. Consecutive patients who underwent resection of an appendiceal orifice lesion using the FTRD were included. The primary outcome was the rate of R0 resection in neoplastic lesions, defined as negative lateral and deep margins on post-resection histologic evaluation. Secondary outcomes included the rates of: technical success (en bloc resection), clinical success (technical success without need for further surgical intervention), post-resection appendicitis, and polyp recurrence. Results 66 patients (32 women; mean age 64) underwent resection of colonic lesions involving the appendiceal orifice (mean [standard deviation] size, 14.5 (6.2) mm), with 40 (61%) being deep, extending into the appendiceal lumen. Technical success was achieved in 59/66 patients (89%), of which, 56 were found to be neoplastic lesions on post-resection pathology. Clinical success was achieved in 53/66 (80%). R0 resection was achieved in 52/56 (93%). Of the 58 patients in whom EFTR was completed who had no prior history of appendectomy, appendicitis was reported in 10 (17%), with six (60%) requiring surgical appendectomy. Follow-up colonoscopy was completed in 41 patients, with evidence of recurrence in five (12%). Conclusions The FTRD is a promising non-surgical alternative for resecting appendiceal lesions, but appendicitis occurs in 1/6 cases.
CRIS-Team Scopus Importer:2021-03-05